The scrum-down on brain damage effects of cumulative mild head injury in rugby: a comparison of group mean scores between national rugby players and non-contact sport controls - Finkelstein, Melissa (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
The present study comprises the second phase of a larger and ongoing research study investigating the brain damage effects of cumulative mild head injury in rugby. The purpose of this study was to determine whether cumulative mild head injury sustained in the game of rugby would cause brain injury as evidenced by impaired performance on sensitive neuropsychological tests. Participants were Springbok professional rugby players (n = 26), Under 21 rugby players (n = 19), and a non-contact sport control of national hockey players (n = 21). Comparisons of performance were carried out across a spectrum of neuropsychological tests for the three rugby groups (Total Rugby, Springbok Rugby, and Under 21 Rugby) versus the performance of the non-contact sport control group (Hockey Control), as well as comparisons of performance f9r the subgroups of Rugby Forwards versus Rugby Backs. Comparisons revealed a consistent pattern of poorer performance across all rugby groups relative to the performance of the controls on tests highly sensitive to the effects of diffuse brain damage. Within rugby group comparisons (Forwards versus Backs) showed significantly poorer performance for Total Rugby Forwards and Springbok Rugby Forwards relative to the performance of the respective Total Rugby Backs and Springbok Rugby Backs on sensitive, as well as on somewhat less sensitive, neuropsychological tests. The performance of Under 21 Rugby Forwards relative to Under 21 Rugby Backs demonstrated similar trends. Brain reserve capacity theory was used as a conceptual basis for discussing the implications of these findings.
Keywords: Sports injuries; Head -- Wounds and injuries; Sports injuries -- Psychological aspects; Neuropsychological tests; Rugby football injuries